Pembentukan Kepribadian Ihsan Peserta Didik Melalui Pembiasaan Aktivitas Keagamaan di MTSN 2 Kota Payakumbuh - Nazif, Muhammad; A, Alimir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This writing is motivated by the very worrying morality of today's young generation. The purpose of writing this scientific work is to determine the formation of students' religious personalities through habituation to religious activities at MTsN 2 Payakumbuh City. The method used in this research is descriptive qualitative, namely describing a situation or event that occurs in the field. The key informant in this research is the Aqidah Akhlak teacher, while the supporting informants are the school principal, deputy head of student affairs and several students. Then in the data collection process, the author used observation, interviews and documentation methods. The data analysis techniques used are data presentation, verification and drawing conclusions. The results of the research concluded that the habit of religious activities can shape the spiritual personality of students at MTsN 2 Payakumbuh City. The strategies used in forming the good personality of students at MTsN 2 Payakumbuh City are habituation strategies, exemplary strategies and law enforcement strategies. Religious activities that are routinely carried out at MTsN 2 Payakumbuh City are shaking hands in front of the gate every morning, praying and reading the Asmaul Husna before studying, midday and Asr prayers in congregation and giving alms every Friday. The ihsan that is formed through the habit of religious activities is: 1) ihsan to Allah: obedience, fear, patience, gratitude, pleasure, honesty, trustworthiness; 2) compassion for humans: courtesy, discipline, helping, appreciating, honoring, cherishing, glorifying, caring socially, and establishing good relationships.